«Conceptually, we should write not about how we won, but about how we fought on a long journey and through losses came to the Great Victory...» - A. A. Zdanovich (Омский научный вестник: Серия "Общество. История. Современность")
Aleksander Aleksandrovich Zdanovich — Doctor of Historical Sciences, professor, veteran of the KGB of the USSR and the FSB of Russia, retired lieutenant general, professor of the Moscow State Pedagogical University, the author of several monographs on the history of Russian special services and the Great Patriotic War. He is one of the founding fathers and president of the Society for the Study of the History of Russian Special Services and active organizer of the scientific conference «Historical Readings in the Lubyanka». This interview was agreed upon during the scientific trip of A. A. Zdanovich to Omsk in September 2020. The interview was given remotely and then edited by Aleksander Aleksandrovich from Moscow in September 2021. The conversation is devoted to the current state and prospects of studying the history of the Russian special services.